Effectiveness, safety and feasibility of an evidence-based insulin infusion protocol targeting moderate glycaemic control in intensive cardiac care units. Issue 2 (1st April 2016) - Avanzini, Fausto; Marelli, Giuseppe; Saltafossi, Donata; Longhi, Chiara; Carbone, Stefania; Carlino, Liliana; Planca, Enrico; Vilei, Veronica; Roncaglioni, Maria Carla; Riva, Emma; ,; Avanzini, F; et al.
Abstract: Objectives: To assess the effectiveness, safety and feasibility of the revised, simplified nurse-managed version of our insulin infusion protocol, adapted to the new recommended glycaemic target of 140 to 180 mg/dL (Desio Diabetes Diagram i.v. 140–180). Methods: All clinical responses to the Desio Diabetes Diagram i.v. 140–180 in use for 3 years were recorded in patients with diabetes or hyperglycaemia admitted to our intensive cardiac care unit. To assess the feasibility, we asked nurses to complete an ad hoc questionnaire anonymously when the new insulin infusion protocol had been in use for 2 years. Results: From December 2010 to December 2013, 276 patients (173 men, median age 75 years) were treated according to the Desio Diabetes Diagram i.v. 140–180. The median time to reach glycaemic target was 4 h (Q1–Q3 2–8) in 128 patients with blood glucose >180 mg/dL and 2 h (Q1–Q3 1–4) in 82 patients with blood glucose <140 mg/dL. Once the target had been reached, insulin infusion was maintained for a median of 38 h (Q1–Q3 24–48) with blood glucose between 140 and 180 mg/dL for 58.3% of the infusion time. Over a total of 11, 863 h of infusion, seven blood glucose <70 mg/dL occurred. The Desio Diabetes Diagram i.v. 140–180 protocol was considered easy to use by 93% of nurses. Conclusions: The Desio Diabetes Diagram i.v. 140–180 protocol, fully managed by nurses, with insulin and glucose intravenous infusion proved effective, safe and feasible in maintaining blood glucose between 140 and 180 mg/dL in patients with diabetes or hyperglycaemia admitted to the intensive cardiac care unit for acute cardiac events.